Digital health transformation with blockchain and artificial intelligence - Chakraborty, Chinmay 1984- (CRC Press, Taylor & Francis Group, 2022)
The book Digital Health Transformation with Blockchain and Artificial Intelligence covers the global digital revolution in the field of healthcare sector. The population has been overcoming the COVID-19 period; therefore, we need to establish intelligent digital healthcare systems using various emerging technologies like Blockchain and Artificial Intelligence. Internet of Medical Things is the technological revolution that has included the element of "smartness" in the healthcare industry and also identifying, monitoring, and informing service providers about the patient’s clinical information with faster delivery of care services. This book highlights the important issues i.e.
1. Blockchain and Internet of Things in Healthcare Systems: Prospect, Issues, and Challenges 2. Secure Digital Health Data Management in Internet of Things using Blockchain and Machine Learning 3. Revolutionizing Healthcare by Coupling Unmanned Aerial Vehicles (UAVs) to Internet of Medical Things (IoMT) 4. Public Perception towards AI-Driven Healthcare and the way forward in the Post-Pandemic Era 5. Security, Privacy issues and challenges in adoption of smart digital healthcare 6. Tapping the Big Data Analytics and IoT in the Pandemic Era 7. The Clinical Challenges for Digital Health Revolution 8. An Overview of Artificial Intelligence for advanced healthcare systems 9. Future Trajectory of Healthcare with Artificial Intelligence 10. Artificial Intelligence and Public Trust on Smart Healthcare System 11. Role of Artificial Intelligence based technologies in healthcare to combat critical diseases 12. Parkinson Disease Pre-Diagnosis Using Smart Technologies:A Review 13. Emerging Technologies to Combat the COVID-19 Pandemic 14. The role of Machine Learning and Internet of Things in Digital Health Transformation 15. Effective Remote Healthcare and Telemedicine Approaches for Improving Digital Healthcare Systems 16. Legal Implication of Blockchain Technology in Public Health
Keywords: Medical informatics; Medicine -- Data processing; Blockchains (Databases); Artificial intelligence; Datenverarbeitung; Blockchain; Künstliche Intelligenz; Medizin